Seroprevalence of Toxoplasma gondii in moose (Alces alces) hunted in Estonia in 2015 - Remes, Noora Helmiina (Eesti Maaülikool, 2017)
Graduation Thesis in Veterinary Medicine Annually around 6000 moose (Alces alces) are hunted in Estonia for human consumption. Moose can host Toxoplasma gondii and their meat can be a source of infection for humans and other hosts. The main aims of this thesis were to estimate the seroprevalence of T. gondii in moose hunted in Estonia and to evaluate different risk factors (age, sex, and geographical location) for seropositivity. Altogether 1004 sampling packages, which included questionnaires, were sent to hunters, who collected 463 blood samples post-mortem from hunted moose. Samples arrived to the laboratory by mail and sera were separated, divided into aliquots and stored frozen until analyzes. A commercial direct agglutination test was used to screen the sera, diluted 1:40, for T. gondii spesific IgG antibodies. We detected serological evidence of exposure to T. gondii in moose in Estonia: 111 moose tested seropositive. The seroprevalence estimate was 23.97%. Female moose had a seroprevalence of 27.53% and male moose 19.63%. Adults had a seroprevalence of 28.80% and calves 12.59%. Seropositive moose were found from all 12 counties where the samples originated. Moose were commonly exposed to T. gondii and the infections appeared to be acquired. Igal aastal kütitakse Eestis inimtoiduks ligikaudu 6000 põtra (Alces alces). Püsisoojaste loomadena on põdrad üheks võimalikuks Toxoplasma gondii peremeheks ja reservuaariks. Lõputöö eesmärgiks oli määrata T. gondii seroloogiline levimus Eestis kütitud põtradel ning hinnata selle erinevaid riskifaktoreid (vanus, sugu ja piirkond). Koostati küsimustik mis lisati välja prindituna selleks uuringuks komplekteeritud proovivõtuvahendite pakendisse. Vabatahtlikkudele jahiseltsidele saadeti kokku 1004 proovivõtuvahendite pakendit. Selleks uuringuks kogusid vabatahtlikud jahimehed kütitud põtradelt surma järgselt 463 vereproovi. Proovid toodi või saadeti posti teel laborisse, kus seerum eraldati, jaotati tuubidesse ja säilitati külmikus kuni analüüsimiseni. ...